Introduction to simulation methods for gas discharge plasmas : accuracy, reliability and limitations - Rafatov, Ismail; Kudryavtsev, Anatoly A. (IOP ebooks. 2020 collection., 2020)
Gas discharge plasma is the most common type of low-temperature plasma, with a large number of practical applications covering almost all areas of modern science and technology. This book is an introduction to the numerical modeling methods for gas discharge plasmas. It is intended to assist and direct graduate students and junior researchers, whose research activity deals with computational plasma physics. Topics covered include the essentials of basic modeling approaches (particle, fluid, and hybrid) for gas discharges, and the implementation of these methods with examples of glow (DC and RF) discharges. Numerical studies of nonlinear dynamics and formation of spatio-temporal patterns in gas discharge systems are also presented.